Prostate cancer-associated urinary proteomes differ before and after prostatectomy. (October 2022) - Feng, Yan; Liu, Shengzhi; Zha, Rongrong; Sun, Xun; Li, Kexin; Wu, Di; Aryal, Uma K.; Koch, Michael; Li, Bai-Yan; Yokota, Hiroki
Background: A wide range of disorders can be detected in the urine. Tumor-modifying proteins in the urine may serve as a diagnostic tool for cancer patients and the alterations in their profiles may indicate efficacies of chemotherapy, radiotherapy, and surgery. Methods: We focused on urinary proteomes of patients with prostate cancer and identified tumor-modifying proteins in the samples before and after prostatectomy. Protein array analysis was conducted to evaluate a differential profile of tumor-promoting cytokines, while mass spectrometry-based global proteomics was conducted to identify tumor-suppressing proteins. Results: The result revealed striking differences by prostatectomy. Notably, the urine from the post-prostatectomy significantly decreased the tumorigenic behaviors of prostate tumor cells as well as breast cancer cells. We observed that angiogenin, a stimulator of blood vessel formation, was reduced in the post-prostatectomy urine. By contrast, the levels of three cell-membrane proteins such as prostasin (PRSS8), nectin 2 (PVRL2), and nidogen 1 (NID1) were elevated and they acted as extracellular tumor-suppressing proteins. These three proteins, given extracellularly, downregulated tumorigenic genes such as Runx2, Snail, and transforming growth factor beta and induced apoptosis of tumor cells. However, the role of NID1 differed depending on the location, and intracellular NID1 was tumorigenic and reduced the percent survival. Conclusions: This study demonstrated that prostatectomy remarkably altered the profile of urinary proteomes, and the post-prostatectomy urine provided tumor-suppressive proteomes. The result sheds novel light on the dynamic nature of the urinary proteomes and a unique strategy for predicting tumor suppressors.